Evaluation of Human Bocavirus (HBoV) as A Cause of Acute Gastroenteritis in Children Under 5 Years: A Case-Control Study (Iraqi Journal of Medical Sciences, 2023)
Background: Acute gastroenteritis (AGE) is the main cause of infants and children's health problems, in developing countries, high morbidity and mortality rates were reported, Human Bocavirus (HBoV) are enteric viruses that linked to cause AGE.Objective: To estimate the prevalence of HBoV infection in children under five years with AGE and to determine its genotypes by using conventional polymerase chain reaction and Sanger sequence. Methods: This is a case-control study, the sample was collected from 100 children under 5 years of age suffering from AGE (as case group) and from 100 asymptomatic control children (as control group) from Central Teaching Hospital of Pediatrics from December 2021 to April 2022. Each children’s stool sample taken was stored at -20°C until they were employed in a conventional polymerase chain reaction to identify the HBoV genotypes.Results: The rate of HBoV infection was found in 10% in AGE case group, while none of control group showed positive result. The genetic analysis showed that six of the investigated samples belonging to the HBoV-2 while four of the investigated samples belonging to the HBoV-3. In HBoV infected children, the age range (1-13 months) had most positive cases 5 (50%) and males had a greater infection rate (80%) than females (20%), however, non-significant association was found in regard to age and sex (P>0.05).Conclusion: A low rate of HBoV DNA was detected in children under five years with AGE suggesting that other pathogen may responsible for infection.Keywords: Human Bocavirus, acute gastroenteritis, children, risk factors, sequencing, phylogenetic tree.Citation: Mohammad MY, Al-Shuwaikh AM, Al-Hamdani HTH. Evaluation of Human Bocavirus (HBoV) as a cause of acute gastroenteritis in children under 5 years: A case-control study. Iraqi JMS. 2023; 21(2): 200-207. doi: 10.22578/IJMS.21.2.8
Keywords: Human Bocavirus; acute gastroenteritis; children; risk factors; sequencing; phylogenetic tree